Compromises and Fairness - Räikkä, Juha (Norwegian University of Science and Technology, 2025)
Many philosophers have pointed out that a compromise that is fair in one sense can be unfair in another. In this paper, I will briefly introduce different ways in which compromises can be “fair” and then analyze them. In particular, I compare the importance of what I call (a) split-the-difference fairness and (b) end-state fairness. I will defend split-the-difference fairness against an important objection—that a person’s false belief about her fair share does not change what her fair share actually is. To allow such a notion would be rather like allowing her false belief to alter what is actually true. Nevertheless, I aim to provide support for the idea that sometimes it may make sense to consider people’s actual beliefs, even if they are false. However, I do not take a strong position on the question of what the most important sense of fairness is with regard to compromises.